Dějiny Biologického ústavu Lékařské fakulty Masarykovy univerzity - Fasora, Lukáš (Masaryk University Press, 2022)
Title in English: History of the Institute of Biology, Faculty of Medicine, Masaryk University A representative book on the history and present of one of the oldest institutes of the Faculty of Medicine of Masaryk University, which has been contributing significantly to the development of biological sciences since its inception.